2022
DOI: 10.1590/1413-81232022272.34942020
|View full text |Cite
|
Sign up to set email alerts
|

Time trend estimation of food consumption in repeated studies with different versions of food questionnaire among Brazilian schoolchildren aged 7 to 11 years

Abstract: Longitudinal study, whose objective was to evaluate of the time trend in food consumption across the 2002-2015 period in schoolchildren aged 7 to 11 years, covered five food surveys in Florianopolis, southern Brazil. Methodological differences across the surveys (typical vs. previous day food consumption, pen-and-paper versus computer screen presentation) and some known risk factors, were adjusted for statistically. Offset by maximum food/beverage consumption per day allowed comparability of a varying number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Food markers signal the healthiness of a population's food consumption, contributing to food and nutritional surveillance 10,21,22 and the formulation and implementation of public policies 10,22 . It is observed that population surveys have included their evaluation in their protocols, even enabling the understanding of the temporal evolution of food consumption 10,23,24,25 and different cuts in the analysis 26 . In times of health emergency, Steele and collaborators 27 analyzed changes in markers of healthy and unhealthy eating when evaluated before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Food markers signal the healthiness of a population's food consumption, contributing to food and nutritional surveillance 10,21,22 and the formulation and implementation of public policies 10,22 . It is observed that population surveys have included their evaluation in their protocols, even enabling the understanding of the temporal evolution of food consumption 10,23,24,25 and different cuts in the analysis 26 . In times of health emergency, Steele and collaborators 27 analyzed changes in markers of healthy and unhealthy eating when evaluated before and during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As we continue to amass large datasets and refine algorithmic techniques, the scope for ML to revolutionize obesity management and prevention is immense. Future avenues for research and application are likely to focus on several key areas that enhance both the precision and effectiveness of interventions [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…By harnessing the power of big data analytics, ML can provide deeper insights into the multifactorial causes of obesity, predicting individual susceptibility with higher accuracy. This precision will allow for the implementation of preemptive measures tailored to individual risk profiles before obesity develops [66][67][68][69]. Secondly, personalized treatment plans based on ML predictions are set to become more nuanced.…”
Section: Discussionmentioning
confidence: 99%